2022
DOI: 10.30773/pi.2022.0092
|View full text |Cite
|
Sign up to set email alerts
|

Development of Korean Version of PTSD Checklist for DSM-5 (K-PCL-5) and the Short Form (K-PCL-5-S)

Abstract: Objective This study presents the reliability and validity of the Korean version of the post-traumatic stress disorder (PTSD) checklist for the Diagnostic and Statistical Manual for Mental Disorders-fifth edition (DSM-5) (K-PCL-5) and the short form (K-PCL-5-S).Methods Seventy-one subjects with PTSD, 74 subjects with mood or anxiety disorders, and 99 healthy controls were enrolled. The Korean version of the Structured Clinical Interview for DSM-5-research version was used to confirm the presence of PTSD. The B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A total score of 33 indicated a provisional diagnosis of PTSD. The Korean version of the PCL-5 was utilized in this study, and it demonstrated good internal consistency and test-retest reliability in the present study (Cronbach’s alpha coefficient of 0.963) ( 17 ).…”
Section: Methodsmentioning
confidence: 79%
“…A total score of 33 indicated a provisional diagnosis of PTSD. The Korean version of the PCL-5 was utilized in this study, and it demonstrated good internal consistency and test-retest reliability in the present study (Cronbach’s alpha coefficient of 0.963) ( 17 ).…”
Section: Methodsmentioning
confidence: 79%
“…It was used in this study to measure the degree of PTSD from the trauma factor of road TAs in participants who underwent the accidents. The Korean version of the checklist, which was translated and verified for its reliability and validity by Kim et al, was used [28].…”
Section: Patient Global Impression Of Change (Pgic)mentioning
confidence: 99%